1986
DOI: 10.1111/j.1440-1681.1986.tb00942.x
|View full text |Cite
|
Sign up to set email alerts
|

Renal Prostaglandin Efflux Induced by Vasopressin, Ddavp and Arachidonic Acid: Contrasting Profile and Sites of Release

Abstract: Prostaglandin (PG) efflux into ureteral (UE) and venous effluents (VE) of rabbit isolated perfused kidneys was determined by superfusion bioassay and radioimmunoassay (RIA), in response to injections of arginine-vasopressin (AVP), the non-pressor vasopressin analogue 1-deamino-8-D-arginine vasopressin (dDAVP) and arachidonic acid (AA). dDAVP (10-1000 ng) failed to stimulate renal PG release, whereas AVP (10-100 ng) and AA (10-50 micrograms) caused a dose-dependent release of PG. AVP evoked PG release into both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1988
1988
2014
2014

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Local biosynthesis of PGE 2 , dependent on both constitutive COX-1 and inducible COX-2 in the kidneys, varies with age and salt intake. It is also affected by several drugs including angiotensin converting enzyme inhibitors 20. PGE 2 produced in the kidneys is excreted as the parent compound and does not affect the pool of metabolites produced by systemic inactivation of PGE 2 21.…”
mentioning
confidence: 99%
“…Local biosynthesis of PGE 2 , dependent on both constitutive COX-1 and inducible COX-2 in the kidneys, varies with age and salt intake. It is also affected by several drugs including angiotensin converting enzyme inhibitors 20. PGE 2 produced in the kidneys is excreted as the parent compound and does not affect the pool of metabolites produced by systemic inactivation of PGE 2 21.…”
mentioning
confidence: 99%
“…The marked postjunctional effect of arachidonic acid would then be possibly due to a production of PGI2 and PGF24. Indeed, in the rabbit kidney (Miller et al, 1986) the main prostaglandins formed from exogenous arachidonic acid infused into the renal artery were PGF2. and PGI2, the latter measured as the stable metabolite PGFj..…”
Section: Discussionmentioning
confidence: 99%
“…They have been shown to be released from the kidney by renal nerve stimulation (RNS) (Needleman et al, 1974) and through activation of al-adrenoceptors by exogenous al-adrenoceptor agonists (Cooper & Malik, 1985). Moreover, prostaglandins can be formed locally in the kidney from exogenous arachidonic acid (Miller et al, 1986). Generally it has been shown that prostaglandins, mainly prostaglandin E2 (PGE2), inhibit noradrenaline release by activating prejunctional inhibitory prostaglandin receptors (Starke, 1977;Hedqvist, 1977).…”
Section: Introductomentioning
confidence: 99%